Riesgos en la administración de inventarios y su incidencia en los estados financieros de las empresas comerciales de la región central del país, en el periodo 2017-2018. - Iza Villagómez, Alba Marina (2019)
The purpose of this researching work is to understand the different types of risks existing in inventory management, so that commercial companies can establish adequate strategies of control procedures that help minimize risks, taking into account that goods represent one of the most important investments of companies in relation to the rest of their assets, since they are fundamental for sales and indispensable for the optimization of profits; this is why the project aims to analyze how the risks of inventories affected the financial statements of commercial companies in the central region of the country, in the period 2017-2018. In order to do this project, the methodology was applied with a qualitative and quantitative approach through bibliographic-documentary and field research, investigated five companies in this sector which provided the required investigative information. With this study, was possible to determine that the risks of the inventories that affect the financial statements are the expiration and life cycle of the products, without affecting a high percentage in relation to the total expenses, income and inventories. The research project produced a different economic impact for each company, since each one of them belongs to different segments according to their size. This is the reason which enterprises need to implement policies and strategies that help them minimize or mitigate inventory risk.